CTNI-09. DIFFUSE MIDLINE GLIOMA-ADAPTIVE COMBINATORY TRIAL (DMG-ACT): A COMBINATION PLATFORM TRIAL IN PEDIATRIC AND YOUNG ADULT PATIENTS WITH DIFFUSE MIDLINE GLIOMA. (14th November 2022) - Franson, Andrea; Kline, Cassie; Molinaro, Annette; Zhang, Yalan; Hitchner, Kelly; Gupta, Nalin; Koschmann, Carl; Prados, Michael; Nazarian, Javad; Mueller, Sabine
Abstract: Despite advances in understanding the biology of diffuse midline gliomas (DMGs), clinical outcomes have not significantly improved. Therapy development is limited by: lack of preclinical data across multiple models and laboratories, limited knowledge about blood-brain barrier penetrance, and lack of multi-agent therapeutic approaches. We aimed to address these limitations by designing and implementing an innovative platform clinical trial (DMG-ACT). DMG-ACT is an open-label, multi-institutional, international trial of combination therapy for patients with DMG between 2 and 39 years of age. This study utilizes a novel Bayesian drug combination platform design with adaptive shrinkage (ComPAS). ComPAS allows for ongoing assessment of therapy efficacy with data borrowing across arms and the ability to eliminate ineffective drug combinations and add new promising combinations throughout the trial. The current treatment arms include ONC201 in combination with paxalisib. Patients enter one of three cohorts: newly-diagnosed (Cohort 1), post-radiation (Cohort 2), and relapsed/progressive (Cohort 3). Each cohort offers a target validation phase for patients who have not yet undergone biopsy to assess intratumoral pharmacokinetics/pharmacodynamics of pre-biopsy, single-agent dosing. Cohorts 1 and 3 offer radiation (Cohort 1) or re-irradiation (Cohort 3) with concomitant single-agent therapy followed by maintenance with combination therapy. The primary efficacy endpoints are median progression-free survival at 6 months (Cohorts 1 and 2) and overall survival at 7 months (Cohort 3). Exploratory endpoints include intratumoral drug concentrations; toxicity profile of combination therapy during radiation; toxicity profile and efficacy of combination therapy; CSF, ctDNA, stool, and flow cytometry biomarker analyses; and health related quality of life, cognitive, and patient/proxy-reported outcome measures. Additional therapy combinations that have shown additive or synergistic benefit in preclinical testing will be incorporated in future trial iterations and several are currently in development. The trial was launched in October 2021, with a total of 21 patients enrolled as of May 2022.